Radiation oncology training in Singapore – A non‐Australasian RANZCR training site. Issue 4 (19th June 2021) - Ho, Francis; Tey, Jeremy; Tseng, Michelle; Ng, Ivy; Tan, Teng Hwee; Lim, Keith; Leong, Yiat Horng; Tham, Ivan WK
Abstract: The Radiation Oncology Department at The National Cancer Institute, Singapore (NCIS) and the Royal Australian and New Zealand College of Radiology (RANZCR) has had a well‐established relationship that began as a partnership to grow a pool of local radiation oncologists to meet a nation's demand for radiotherapy services. This journey has surpassed its initial aims and now has produced a generation of radiation oncologists leading a national cancer institute. We recount the history and progress of this partnership here, as well as the unique success of its product; the only RANZCR‐accredited radiation oncology training site outside of Australia and New Zealand since 2002. We outline the mutual benefits through many years of collaboration and deliberate efforts to grow the partnership. We also outline the distinctive specialist training path that our trainees take to meet both the local accreditation body as well as the RANZCR requirements.